Stort fald i dansk eksport, men sammensætningen kan være en stødpude - Adrian Michael Bay Schmith; Helle Eis Christensen (Danmarks Nationalbank, 2020)
– Danish exports are expected to decline significantly in the coming quarters. However, the composition of Danish exports might ease the fall. Exports of goods account for the majority of Danish exports and are less affected as they largely consist of less cyclical goods. More cyclically sensitive exports are also more employment intensive, and hence employment in export-oriented industries will be hit harder than the actual value of exports.
Keywords: 330; Export; Außenhandelsstruktur; Exportwirtschaft; Dänemark